Regenerative Backscatter Transponder Using the Switched Injection-Locked Oscillator Concept - Vossiek, Martin; Schäfer, Tobias; Becker, Dirk (IEEE MTT-S International Microwave Symposium 2008 (IMS 2008), 2008)
In this paper, a new backscatter transponder type is introduced. The developed transponder regenerates a modulated, phase-coherent high-power response/ replica to an interrogating CW radar signal. To create the amplified phasecoherent transponder response, the switched injection locked oscillator (SILO) concept is applied. Compared with a usual passive backscatter transponder - known e.g. from UHF RFID systems - the reading range of a SILO transponder is substantially increased. It is demonstrated that a reading range above 20 m is easily obtained even with a 5.8 GHz, 15 MBit/s system. © 2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.regene
Keywords: Identification; Oscillators; Phase synchronization; Radar; Radio communication; Transponders